Sex as an Independent Prognostic Factor in a Population-Based, Non-Small Cell Lung Cancer Cohort. Issue 1 (2013) - Pitz, Marshall W; Musto, Grace; Navaratnam, Srisala
Abstract : BACKGROUND: Males with non-small cell lung cancer (NSCLC) tend to experience worse outcomes, as do those with nonadenocarcinoma histology; however, the independent effects of these factors remain unclear. OBJECTIVE: To evaluate the independent effect of sex and histology on mortality in a population of patients with NSCLC. METHODS: All patients with NSCLC in Manitoba from 1985 to 2004 were identified from the Manitoba Cancer Registry. Treatment data were extracted from the Manitoba Health administrative databases and linked to the registry. Cox regression analysis was used to determine the independent effect of sex on survival. RESULTS: A total of 10, 908 patients (6665 male, 4243 female) with NSCLC were identified. Females had a median overall survival of 9.4 months versus 6.8 months for males (P<0.001). The adjusted HR for death for males compared with females was 1.13 (95% CI 1.04 to 1.23; P=0.004). Sex modified the effect of surgical treatment on survival (HR 1.26 [95% CI 1.13 to 1.40]; P<0.001). Adenocarcinoma histology modified the effect of sex on survival (HR 1.36 [95% CI 1.24 to 1.50]; P<0.001) when treatment was accounted for. CONCLUSION: Females experienced a significantly better survival rate than males independent of treatment, age, year of diagnosis and histology. This was greatest in surgically treated patients and in those with adenocarcinoma.